Three mb. Vogt-koyanagi-harada cases in Slovenia - Nataša Vidovič-Valentinčič; Jelka Brecelj; Matej Beltram; Aleksandra Kraut (Zdravniški Vestnik, 2005)
Background: To describe diagnostic criteria, clinical manifestations and course of disease in patients with Mb. Vogt-Koyanagi-Harada (VKH), examined and treated at the University Eye Clinic in Ljubljana. Patients and methods: We included all patients diagnosed with VKH, who were treated at the University Eye Clinic in Ljubljana. Their history, results of examinations and diagnostic tests as well as the received treatment and outcome were reviewed and compared. Results: We present three patients with VKH, a woman and two men, aged 26, 30 and 40 years at time of disease onset. In all cases eye involvement was bilateral, there was no history of penetrating ocular trauma or surgery preceding the initial onset if uveitis, there were no clinical or laboratory evidence suggestive for other uveitic entities. The diagnosis was established on the ground of ocular and systemic signs. Conclusions: VKH is as expected to be a rare disease in Slovenia as it is linked with certain ethnical and racial groups.